Psychometric evaluation of Life Attitude Profile Scale-Revised in Patients with Cancer - Ghaffari, Fatemeh; Fotoukian, Zahra (Advances in Nursing & Midwifery, 2016)
Abstract: Background and Aim Increasing life expectancy and improving the quality of life of patients with cancer is one of the health priorities. The attitude towards life is one of the most important effective factors. The objective of present study was psychometric evaluation of revised life attitude scale in cancer patients undergoing chemotherapy. Materials and Methods This was a methodological study. 138 patients with cancer patients undergoing chemotherapy have been selected by simple random sampling. First, the scale was translated to Persian. Internal consistency was estimated using Cronbach’s coefficient alpha. The validity was determined by constructed validity using exploratory factor analysis exploratory, content validity (by calculating content validity index and content validity ratio) and also face validity. Results Results of factor analysis showed six essential factors as the basis of Persian life attitude profile-revised scale. The first factor (goals) explained the main portion of variance of scale’s questions. The index of Kaiser-Meyer-Olkin showed the adequacy of sample size. (0.601). Content validity index was 0.79-0.85. The content validity ratio for the above choices of scale was equal to +0.99 (p<0. 05). Conclusions According to the results of this study the Persian version of life attitude in patients scale in cancer patients had appropriate validity and reliability. The mentioned tool is also suitable for researches and useful as a screening tool in clinical environments. Keywords: Attitude; Reliability and Validity; Cancer; Scales